Pengaruh Kualitas Pelaksanaan Islamic Corporate Governance dan Kompleksitas terhadap Frekuensi Terjadinya Fraud pada Perbankan Syariah di Indonesia - Suharto; Dominicus Savio Priyarsono; Trias Andati (Department of Islamic Economics, IPB University, 2022)
This study is explore the quality of ICG in sharia banking in Indonesia during the period of 2011 – 2020, analyze the effect of the quality of ICG implementation and complexity on the frequency of fraud in sharia banking in Indonesia. This study uses a descriptive method with a quantitative approach. The data analysis method used panel data regression. The results that the quality of ICG implementation at BUS during 2011-2020 on average was in the predicate of “very good”, “good” and “good enough”. The implementation of ICG in BUS BUKU III is better than BUS BUKU II and BUKU I. The results also show that the quality of ICG implementation has a significant effect on fraud, if the ICG value increases (the quality of ICG implementation decreases) by 1 unit, then fraud will increase by 1.3251 unit. Then, the complexity has no effect on the frequency of fraud, meaning that the complexity of banks reflected in the category of BUKU 1 banks has the same level of fraud as BUKU II and III.